Administering a GnRH agonist (receptal) after insemination fails to improve pregnancy rates at first service - Rettmer, I.; Stewart, R.E.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2011)
Two experiments were performed to determine the influence of administering a highly potent agonist of gonadotropin-releasing hormone (Receptal) on various reproductive characteristics in dairy cows. In Experiment 1, lactating Holstein cows were treated with either saline (n = 51) or 8 μg of receptal (n = 50) on d 11 to 14 after estrus (d 0) and first service. Peak concentrations of LH, FSH, and progesterone, but not estradiol-17b, in blood serum were increased during 6 to 12 h after injection of Receptal. Pregnancy rates were unaffected by treatment. Concentrations of progesterone in blood serum were increased in nonpregnant and pregnant cows after injection of Receptal. Return to estrus in Receptal-treated cows increased by 2.5 ± .8 days compared to controls. The number of follicles >10 mm in diameter, assessed by transrectal ultrasonography, were reduced and follicular development was altered after Receptal. In Experiment 2, various doses of Receptal were tested in eight dairy herds, including 1,013 inseminations at first service. Cows were given a single injection of either saline or 4, 8, or 12 μg of Receptal on days 11 to 14 after first service. Pregnancy rates were not improved consistently in all herds and failed to increase across all herds. We concluded that administering a potent GnRH agonist altered number and distribution of ovarian follicles, increased cycle length, and increased concentrations of progesterone, without a consistent increase in fertility.
Keywords: GnRH agonist; Pregnancy rates; Hormones; Cattle